H υστερορωμαϊκή καταγωγή των εθίμων του Κατακλυσμού στην Κύπρο. Μια νέα υπόθεση εργασίας - ΔΕΛΗΓΙΑΝΝΑΚΗΣ, Γεώργιος (Byzantina Symmeikta, 2021)
It is here argued that the three-day festivities of the Holy Spirit/ Pentecost in Cyprus, known as Kataklysmos, being first reported by the mid-18th century and being celebrated up to our days, have their roots in Late Roman festivals: namely, the Rosalia, dedicated to the dead’s memory and the spring festival of Maioumas, associated with the sea. Apart from striking similarities with the Pentecost celebrations, both festivals (in a depaganised form) survived into the Byzantine times. Together with Pentecost, they were celebrated at around the same time of the year. Previous theories regarding the possible roots of these folklore customs are here challenged.